Do Dimensions of TC Treatment Predict Retention and Outcomes? - Mandell, Wallace (2008)
First week Dimensions of Change Instrument (DCI) assessments from a cohort of 519 adults entering six TCs were used to predict treatment retention and outcomes. More positive first week response to TC social processes, Community Responsibility; Resident Sharing Support and Enthusiasm; Group Process; and Clarity and Safety, and to one TC personal development process, Positive Self-Attitude and Commitment to Abstinence, predicted retention for the first month. Improvement at 30 days in Clarity and Safety and Resident Sharing, Support and Enthusiasm scores predicted retention in treatment for 3, 6 and 9 months. In multivariate analyses available for a subset of the entry cohort, longer tenure in treatment was a robust predictor of post-treatment outcomes. First week DCI scores on the community process scales predicted post-treatment AOD abstinence and functioning.